現代性視域中的晚清小説研究: A Study of Late Qing Fiction from the Perspective of “Modernity”
<span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. 晚清小説研究一直是中國現代文學研究的一個重要領域，魯迅、胡適、米列娜、陳平原、王德威等學者或以晚清小説爲“他者”，討論“五四”文學的現代性，依此分析中國小説由“傳統”向“現代”的進化；或通過對晚清小説的結構分析，在比較文學或比較文化的層面，重估晚清小説的現代性意義；或通過對“晚清小説的現代性”的論證挑戰中國現代文學的“五四起源論”，回應人文學界有關“多元現代性”的討論。晚清小説在不同時期的研究視域中呈現的不同意義，既體現出研究者問題意識與批評方法的差異，亦凸顯出包括文學研究在内的人文學科在二十世紀的不同文化政治語境中的深刻變革。 The study of the fiction of the late Qing period (1894-1911) is an important area in the field of modern Chinese literature. In their discussion of the “modernity” of May Fourth literature, scholars such as Lu Xun (1881-1936), Hu Shi (1891-1962), Milna Delezelova-Velingerova, Chen Pingyuan, and David Der-wei Wang defined late Qing fiction as “the other” and used it as a demarcation between the “traditional” and “modem” in the evolution of Chinese fiction. In their research into comparative literature and comparative culture, some scholars have reevaluated the significance of the modernity of late Qing fiction through an analysis of its structures. Through their study of the modernity of late Qing fiction, some scholars have challenged the view that modem Chinese literature originated from the May Fourth Movement. This was in fact a response to the discussion of “multi-faceted modernity” in humanities scholarship. Late Qing fiction assumes a different significance depending on the research angle and time-period. This phenomenon reveals discrepancies in researchers’ approach and methods of criticism. It also highlights the profound transformation of the humanizes, which include literary studies, in different cultural-political contexts of the twentieth century. , journal=人文中國學報, author=李楊, year=2011, month=Sep., pages=263–296